In-flame spheroid formation from non-spherical slag particles – A numerical and experimental study. (April 2020) - Gerhardter, H.; Knoll, M.; Raic, J.; Prieler, R.; Landfahrer, M.; Hochenauer, C.; Tomazic, P.; Schroettner, H.
Highlights: Specialized drag and particle heat transfer models were used. The key factors for spheroid formation were investigated. Numerical methods to predict the product quality have been found. The impact of particle size and shape was investigated. Particles were mostly heated due to convection. Abstract: In order to identify the key factors for successful and efficient production, the formation of spherical particles from highly non-spherical coal slag grains was investigated within this work. The main focus was on precise drag and heat transfer calculations in order to obtain suitable criteria to predict the later product quality. State-of-the-art combustion, radiation and multiphase models in combination with specially adapted closure relations for drag and heat transfer were used for this purpose. The second objective was to investigate the relationship between particle temperature, viscosity, surface tension, shape and time required by the particles to obtain a smooth, round surface while passing through the burner chamber. In the first step, the process was investigated in experimental work. Slag particles were injected into an experimental furnace with a thermal input of 70 kW. The slag particles heated up which caused a reduction of slag viscosity by several orders of magnitude. While passing through the furnace, the sharp-edged powder grains transformed into smooth, highly spherical particles due to their surface tension. Numerical calculations were used to identify the main influence factors of in-flame spheroid formation. The effects of particle temperature, size, initial shape and residence time on the sphericity of the particle were studied using a Volume of Fluid (VOF) multiphase model and single-particle simulations which allowed calculations of the interface between an isothermal particle and the surrounding gas phase, as well as the interface deformation due to surface tension. The calculations have shown, that particles with volume-equivalent diameters in the range 420 µm-840 µm and an initial sphericity of 0.65 transform to spheroids in timescales in the order of 10 −1 – 10° s when heated to temperatures above 1373 K. The critical particle temperature value of 1373 K was also confirmed by Euler-Lagrangian calculations of the reactive multiphase flow in the furnace. It has been shown that the particle peak temperature is a sufficient criterion for the formation of spheroids from highly non-spherical particles and that fluid temperature and particle residence time are the most important parameters of the later production process.